Corner‐Sharing Tetrahedrally Coordinated W‐V Dual Active Sites on Cu2V2O7 for Photoelectrochemical Water Oxidation - Huang, Zheng‐Yi; Chen, Yi‐Ying; Hao, Le‐Yang; Hua, Ying‐Jie; Lei, Bing‐Xin; Liu, Zhao‐Qing (Small (Weinheim an der Bergstrasse, Germany), 2024)
The sluggish four‐electron oxygen evolving reaction is one of the key limitations of photoelectrochemical water decomposition. Optimizing the binding of active sites to oxygen in water and promoting the conversion of *O to *OOH are the key to enhancing oxygen evolution reaction. In this work, W‐doped Cu2V2O7 (CVO) constructs corner‐sharing tetrahedrally coordinated W‐V dual active sites to induce the generation of electron deficiency active centers, promote the adsorption of ─OH, and accelerate the transformation of *O to *OOH for water splitting. The photocurrent obtained by the W‐modified CVO photoanode is 0.97 mA cm−2 at 1.23 V versus RHE, which is much superior to that of the reported CVO. Experimental and theoretical results show that the excellent catalytic performance may be attributed to the formation of synergistic dual active sites between W and V atoms, and the introduction of W ions reduces the charge migration distance and prolongs the lifetime of photogenerated carriers. Meanwhile, the electronic structure in the center of the d‐band is modulated, which leads to the redistribution of the electron density in CVO and lowers the energy barrier for the conversion of the rate‐limiting step *O to *OOH. The constructed corner‐sharing tetrahedrally coordinated W‐V dual active sites in W‐doped Cu2V2O7 produce electron deficiency active centers, which promote the adsorption of –OH and accelerate the transformation of *O to *OOH for water splitting.